Financial resilience of conventional versus participation banking: Evidence from macro stress testing approach and risk spillovers analysis - Atan, Huzeyfe Zahit (Graduate School, 2022)
Islamic banking, which provides an alternative to the traditional banking system through the principals of interest-free finance, has risen in global markets over the last 20 years and is already present in many countries. Rising consumer demand for Islamic-law-based products and services has propelled Islamic banking to the forefront of the global economy during this period. Another factor that may appeal to investors is the approach Islamic banking manages financial risks. Several studies that showed, during the 2008 global recession, Islamic banks outperformed their conventional counterparts suggesting that the Islamic banking system may be a safe haven for global risk spillovers. In that regard, several studies have been performed to compare and contrast conventional and Islamic banking. In light to these advances in Islamic banking, this dissertation is made up of three chapters that compare Islamic and conventional banks on a worldwide scale as well as in the context of Turkey. In the first chapter, we examine how equity returns of conventional and Islamic banks are affected by shocks to major financial indices using the multivariate quantile autoregression technique. We analyze the resilience of the dual banking systems to financial risk spillovers at the global and regional levels based on data from 16 countries for the period between 2008-2018. The primary goal of this research is to see if there is a link between key financial indices and bank stock prices, as well as to compare conventional and Islamic banks in this regard. Recent research has found that bank stock price is linked to banks' overall performance. In this regard, bank stock performance is critical in terms of providing information about the bank's overall success. The findings of the first chapter show that there is no substantial difference in sensitivity to financial shocks between Islamic and conventional banks at the global and regional levels. As a result, this conclusion may suggest that Islamic markets have lost their safe haven status over interest-based financial systems since the 2008 financial crisis. Moreover, in contrast to earlier reports on Islamic banking competitiveness that argue that double layers of Shariah systems may generate heterogeneity across countries, our results reveal that the effects of individual shocks to Islamic banks are homogeneous in the Gulf, MENA, and Asian countries. This uniformity may be attributable, among other things, to recent advancements in Islamic financial principles and standards released by AAOIFI and IFSB. Second chapter extends the data timeline in first chapter to investigate stability and risk characteristics of dual banking system using 170 banks from 14 emerging market countries with multivariate quantile regression technique for 2008-2020 period. The primary purpose of this chapter is to examine how bank-specific factors influence risk spreads on conventional and Islamic banks' stock price returns. For this purpose, we choose leverage ratio, capital adequacy ratio and market value as bank specific determinants. Our findings reveal that bank equity prices tend to be more sensitive to shocks in major financial indices as bank's leverage ratio increases for both Islamic and conventional banks. This result is important especially for Islamic banks as recent reports claim that recently developed instruments in Islamic financial system which have led to increases in the debt and leverage ratio, endangers stability of the Islamic banks as they are relatively more affected to financial risk spillovers. For bank size, the impact of financial shocks over bank equity returns increases with bank size for Islamic banks. The primary cause might be that when Islamic banks increase in size, credit risk management gets more complex owing to specific risk management requirements for different PLS transactions which may cause moral hazard and adverse selection concerns. However, we observe the impact of the financial shocks doesn't vary according to different bank size levels for conventinal banks. Last, our findings imply that when the capital adequacy ratio reduces for conventional banks, they become more vulnerable to financial shocks. Third chapter compares determinants of capital adequacy requirements for participation and conventional banks in Turkey employing an innovative stress test approach. We use two models for our analysis: an additive semi-parametric quantile regression model (Koenker 2010,2011) and a semi-parametric quantile panel model (Cai et al (2018). Also, with probability analyses, the likelihood of capital adequacy ratio being lower or greater than a given value is calculated based on values of explanatory factors in the context of various scenarios. The public debt ratio for conventional banks and the exchange rate for Islamic banks are the key drivers in establishing the capital adequacy ratio, according to the findings in the third chapter. Although unemployment has a positive marginal impact on the capital adequacy ratio in both Islamic and conventinal banks, the results imply that this positive impact is unaffected by the fluctuations in the unemployment rate. The semi-parametric panel quantile technique is used only for conventional banks, as there are very few banks for Islamic banks in our sample, and the determinants of capital adequacy ratio are explored while taking bank size into account. Banks improve their capital adequacy ratios regarding increases in the public debt ratio and interest rate as their size and capital adequacy grow
Konvansiyonel bankacılık ve katılım bankacılığının finansal dayanıklılıklarının karşılaştırılması: Makro stres testi ve risk yayılımı analizi yaklaşımları
Thesis(Ph.D.) -- Istanbul Technical University, Graduate School, 2022
Keywords: banking; bankacılık; macro stress testing; makro stres testi